2018
DOI: 10.1002/ejlt.201800158
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Comparison of Lipid Composition, Oxidation Stability, and Antioxidant Capacity of Sesame Oil: An Industrial‐Scale Study Based on Oil Extraction Method

Abstract: Sesame oils are widely consumed around the world, but a study on their lipid composition, oxidation stability, and free radical scavenging capacity is limited. In this article, characterizations of 13 sesame oils extracted by four different processing techniques are evaluated. The results show that triacylglycerol and fatty acid compositions are not significantly affected by the oil extraction technology. However, differences in minor component composition, oxidation stability, and free radical scavenging capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…A methanol extraction procedure was used to obtain the polar fraction of the samples according to a previously published method [ 47 ] with the following modifications: 2.5 g of SWSO was mixed with 5 mL of methanol, vigorously shaken for 20 min in the dark, and then centrifuged at 2148 × g for 10 min (H1750R, Cence Instrument Development Co., Ltd., Hunan, China). The extraction process was repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…A methanol extraction procedure was used to obtain the polar fraction of the samples according to a previously published method [ 47 ] with the following modifications: 2.5 g of SWSO was mixed with 5 mL of methanol, vigorously shaken for 20 min in the dark, and then centrifuged at 2148 × g for 10 min (H1750R, Cence Instrument Development Co., Ltd., Hunan, China). The extraction process was repeated three times.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, a variety of transcription factors and downstream genes have been confirmed closely related to these processes, such as peroxisome proliferator-activated receptors (PPAR), liver X receptor α (LXRα), and cholesterol 7α hydroxylase (CYP7A1) (Majdalawieh & Ro, 2015;Sharma et al, 2012;Zhang, Yu, Hu, et al, 2016). According to the results of our previous investigations, although the content of sesamol (not detected-0.31 mg/g) was lower than sesamin (2.07-7.51 mg/g) in sesame oils, it exhibited higher antioxidative activity and free radical scavenging capacity, possessing a significantly positive correlation (p < .01) with the oxidative stability of sesame oil Shi, Zheng, Zhang, et al, 2018). Recently, Qin et al (2019) observed that sesamol showed ameliorative effects on obesity-associated metabolic disorders by regulating hepatic lipid metabolism.…”
Section: Introductionmentioning
confidence: 92%
“…Based on sesame seed oil processing methods, sesame seed oils in China can be divided into four types, including: (1) pressed fragrant sesame seed oil, (2) ground fragrant sesame seed oil, (3) cold-pressed sesame seed oil and (4) refined sesame seed oil [15,16]. These types of sesame seed oils, mainly pressed fragrant sesame oil and ground fragrant sesame oil, have different aroma flavors based on the different processing methods.…”
Section: Analysis Of β-Carbolines In Fragrant Sesame Seed Oilsmentioning
confidence: 99%
“…Therefore, it was found that the levels of β-carboline compounds (harman and norharman) in ground fragrant sesame seed oils were lower than the levels of β-carbolines (harman and norharman) in pressed fragrant sesame seed oils (see Figures 1 and 2). Compared with pressed fragrant sesame seed oil and ground fragrant sesame seed oil, cold-pressed sesame seed oil only requires drying the sesame seed at mild heating temperature (<80 • C) before the sesame seed pressing process [16]. Notably, coldpressed sesame seed oils do not belong to the flavor edible oils (e.g., fragrant sesame seed oils).…”
Section: Pressed Fragrant Sesamementioning
confidence: 99%
See 1 more Smart Citation